The Moderation Effect of Allowance for Impairment of Credit Losses Toward Credit Growth and Profitability - Angga Nugraha (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to examine the Allowance For Impairment Of Credit Losses in moderating the relationship between credit growth and non-performing loans to profitability. The population in this study are all commercial banks listed on the Indonesia Stock Exchange in 2019-2022. purposive sampling is the sampling method used in this study. data were analyzed by PLS-SEM. The test results show that credit has an effect on ROA while NPL does not. Allowance For Impairment Of Credit Losses moderates the relationship between NPL and ROA.